Điều khiển PID hai mức với điều kiện hạn chế modan - Vinh, Thái Quang (Journal of Computer Science and Cybernetics, 2016)
The problem dealt with in this paper is synthesis of two - level optimal PID control, which is at the first level to solve Riccati equation on PC and at the second to calculate optimal control variable on micro-controller. The proposed algorithm of this two - level PID will guarantee the quadratic performance index and desired arrangement of poles and zeros of closed system (so-called mod an limitation).